2001
DOI: 10.1016/s0893-133x(01)00340-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiological Basis of Female-Specific Mood Disorders

Abstract: Women have twice the incidence of major depression compared with men. They are prone to develop episodes of depression during times of reproductive hormonal change at puberty, with use of oral contraceptives, during the premenstrual phase of the menstrual cycle, postpartum and during the perimenopause (see review: Parry 1995a). WirzJustice (1995) In women, hormonal changes associated with the reproductive cycle may provoke affective changes in predisposed individuals. Examples include depression associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 39 publications
0
63
1
7
Order By: Relevance
“…Given the mean age of our female participants falling around the menopausal period (Ϸ55 years), we can speculate that the periods marking shifts in the reproductive stages, such as menopause, are particularly vulnerable times for women, because they are associated with major hormonal turmoil and psychosocial stresses that may, in turn, lead to adverse health outcomes. 27 For example, in our sample of female participants, the prevalence of depression cases was higher among women reporting short duration of sleep (Յ5 hours per night) than in other subgroups. In addition, as shown in our descriptive analyses, the distribution of correlates of short sleep duration that have the potential to affect hypertension risk was different between genders and may have partially contributed to the observed associations.…”
Section: Strengthsmentioning
confidence: 58%
“…Given the mean age of our female participants falling around the menopausal period (Ϸ55 years), we can speculate that the periods marking shifts in the reproductive stages, such as menopause, are particularly vulnerable times for women, because they are associated with major hormonal turmoil and psychosocial stresses that may, in turn, lead to adverse health outcomes. 27 For example, in our sample of female participants, the prevalence of depression cases was higher among women reporting short duration of sleep (Յ5 hours per night) than in other subgroups. In addition, as shown in our descriptive analyses, the distribution of correlates of short sleep duration that have the potential to affect hypertension risk was different between genders and may have partially contributed to the observed associations.…”
Section: Strengthsmentioning
confidence: 58%
“…For example, light has been employed (often during the daytime) to treat seasonal affective disorder, depression in women with pre-menstrual disorder (Parry and Newton 2001), to regulate menstrual cycles (Lin et al 1990), and to improve activity levels of patients with dementia (Holman 2010) by manipulating the onset of melatonin production. Less tangible is an apparent sense of wellbeing humans may instinctively feel in lit environments, even where their physical wellbeing may be unaffected or harmed, possibly a response evolved due to increased predation risk in dark areas in naturally lit environments (Packer et al 2011).…”
Section: Human Health and Wellbeingmentioning
confidence: 99%
“…49 Women with PMDD have abnormal melatonin secretion and other circadian system abnormalities. 56 It has been proposed that women with PMDD have altered affective information processing and regulation during the luteal phase, with abnormal activation patterns in specific brain regions. 55 Imaging studies have demonstrated altered functional magnetic resonance imaging responses to negative and positive stimuli in the orbitofrontal cortex, amygdala and ventral striatum in women with PMDD compared with control subjects.…”
Section: Etiologymentioning
confidence: 99%
“…188 It has been proposed that sleep deprivation and light therapy may decrease premenstrual dysphoria by correcting abnormal circadian rhythms found in women with PMDD. 56 Although a crossover study reported that evening bright light for 2 premenstrual weeks decreased depression and tension, 189 a meta-analysis of the few existing trials suggested a small effect size for bright light therapy.…”
Section: Herbal Complementary and Other Treatmentsmentioning
confidence: 99%